Assessment of Weight Gain Post Treatment with Biological Compounds among A Sample of Patients Attending Baghdad Teaching Hospital - mousa, ata (Iraqi National Journal of Nursing Specialties, 2016)
Objective: to evaluate the increase in weight after biological agents and the association of weight gain with the body mass index among a sample of patients attending Baghdad Teaching Hospital Methods: A prospective study is carried out in Baghdad teaching hospital biological units and outpatient clinic of rheumatology for a period of one year starting On April 2015 and ending on March 2016. 120 patients were included in the study 40 psoriatic arthritis .40 ankylosing spondylitis and 40 rheumatoid arthritis Results : The study findings indicate that significance differences are seen regarding weight gain and biological agents (Infliximab, Etanercept and Adalimumab after one year of follow up of patients with psoriatic arthritis rheumatoid arthritis, ankylosing spondylitis respectively ,highest percentage of weight gain was reported with inflximab and psoriatic arthritis with a mean differences of BMI and weight (7.34&12.85) respectively while lowest percentage of weight gain was reporter with Etanercept and Rheumatoid arthritis with a mean differences of BMI ant weight(5.94 &8.61) respectively Recommendations: The study recommends further studies on the relation between weight gain and biological therapies and how and why this medication causes this weight change and what can be done to explore the real reason for these increments in weight of patients